Ado-tratuzumab emtansine beyond breast cancer: therapeutic role of targeting other HER2-positive cancers - Yang Zheng; Jiayu Zou; Chen Sun; Fu Peng; Fu Peng; Cheng Peng (Frontiers in Molecular Biosciences, 2023)
Ado-trastuzumab emtansine (T-DM1) is an antibody–drug conjugate approved by the FDA in 2013 for advanced HER2-positive breast cancer treatment exhibiting promising clinical benefits. However, HER2 overexpression and gene amplification have also been reported in other cancers like gastric cancer, non-small cell lung cancer (NSCLC), and colorectal cancer. Numerous preclinical studies have also revealed the significant antitumor effect of T-DM1 on HER2-positive tumors. With the advancement in research, several clinical trials have been conducted to investigate the antitumor effect of T-DM1. In this review, we briefly introduced the pharmacological effects of T-DM1. We reviewed its preclinical and clinical studies, especially on other HER2-positive cancers, establishing what has been encountered between its preclinical and clinical studies. In clinical studies, we found that T-DM1 has a therapeutic value on other cancers. An insignificant effect was observed on gastric cancer and NSCLC, inconsistent with the preclinical studies.